Determinants of hazardous alcohol use among pregnant women attending antenatal care at public health facilities in Gondar town, Northwest Ethiopia: A nested case-control study. - Alemu Earsido Addila (Public Library of Science (PLoS), 2021)
Background Alcohol use during pregnancy has a potential negative impact on the health of women and children. Binge or hazardous drinking may do greater alcohol-related damage to the developing fetus than drinking a comparable amount spread over several days or weeks. This study aimed to identify determinants of hazardous alcohol use among pregnant women attending antenatal care at Gondar town public health facilities, Northwest Ethiopia. Methods An unmatched facility-based nested case-control study was carried out to identify the determinants of hazardous alcohol use among pregnant women within a prospective cohort study from 29 October 2019 to 7 May 2020. A two-stage random sampling technique was used to select 455 (113 cases and 342 controls) pregnant women. Data collection was performed using the AUDIT-C standardized and pretested questionnaire. Bivariable and multivariable logistic regression analyses were computed to identify the predictors of alcohol consumption using the odds ratio, 95% CI, and p-value < 0.05. Results Multivariable logistic regression model revealed that no formal education of the husbands [AOR = 2.79; 95%CI: 1.24, 6.29], being housewife[AOR = 2.43; 95%CI: 1.12, 5.26], poor household wealth index[AOR = 2.65; 95%CI: 1.07, 6.54], unplanned pregnancy [AOR = 4.36;95%CI: 2.44, 7.79], poor social support [AOR = 4.9;95%CI: 2.4, 10.04], depression[AOR = 3.84;95%CI: 2.16, 6.82], and not ever heard the risk of alcohol drinking during pregnancy [AOR = 1.97; 95%CI: 1.08, 3.58] were significantly associated with hazardous alcohol use. Conclusions Routine alcohol screening during ANC visits creates an appropriate referral system for clinical management and provides an opportunity for healthcare workers to offer information on the potential risks associated with alcohol use in pregnancy. Antenatal care providers have a special role to play in assuring that women receive adequate advice about alcohol use and care to manage the problems especially for pregnant women with depression, poor social support, unplanned pregnancy, low socioeconomic status, and for housewives during the antenatal visits. The warning marks on alcoholic beverages including an ongoing message about the risks of alcohol use during pregnancy could be public health good strategies to minimize preventable harms attributed to alcohol consumption during pregnancy.